Is Thought Outside Language Possible? - Saukaitytė, Dalia (Problemos, 1982)
The methodological content of the assumption on the occurrence of “nonverbal” thinking is observed. The above assumption arises when the methodological (philosophical) aspect of study is substituted for a special-scientific one, i.e., when the relation between language and thought is observed as a relation of two absolutely independent, genetically unrelated phenomena, when thought is considered a mere “ability” of an individual. Consistently applying the Marxist methodology to analyse the links between thought and language, the problem of “nonverbal” thinking does not arise.